Polybenzimidazole membranes with an ionic conductivity of 500 mS cm-1 and an alkaline water electrolysis performance of 1.9 A cm-2 @ 1.8 V - Muhammad Luthfi Akbar Trisno; LEE SU JI; Fatemeh Sanaz Razmjooei; Syed-Asif Ansar; Artur Michalak; Park, Hyun S.; Dirk Henkensmeier ((사)한국전기화학회, 2021)
KOH doped polybenzimidazole as a type of ion solvating membrane is a promising system in alkaline water electrolysis. It has better performance than Zirfon, a commercial alkaline water electrolysis separator, because of the lower area resistance.[1] In this work, the conductivity of PBI was optimized. For this, casting of polybenzimidazole was carried out by dissolving it in phosphoric acid, followed by KOH doping without intermediate drying. Fully swollen gel-state membranes were obtained,[2] with over 400% total uptake of KOH and water. Conductivity of these membranes can be as high as 500 mS cm-1in 25wt% KOH solution, one of the highest reported conductivities, far exceeding that of DMAc casted polybenzimidazole, which is in the range of 100 mS cm-1.[3] The morphology of these membranes was investigated. To increase membrane strength, PBI was reinforced with a porous PVDF support. This reduced the conductivity to 227 mS cm-1 in 25wt% KOH solution, which is still twice higher than for standard PBI used so far in the literature. The conductivity was stable and did not decrease after 8 weeks storage. Tensile strength and Young modulus were 5.5 MPa and 104.9 Mpa, respectively. Bubble point tests were conducted up to the maximum system pressure of 5.6 MPa, indicating safe use in an electrolyser system. To further improve stability and avoid alkaline degradation of the PVDF support, also Teflon-supported membranes were investigated. In a water electrolysis test with plasma-sprayed Raney nickel-based electrodes, PVDF/PBI exhibited 1.9 A cm-2 at 1.8 V. To the best of our knowledge, this is the best result ever reported for alkaline water electrolysis with non-platinum group catalysts.[1]
Keywords: water electrolysis; Polybenzimidazole; gel-state; KOH; membrane